MAKNA BILANGAN ANGKA DALAM AL-QUR'AN - Misbahudin, Iing (At-Taqaddum, 2011)
The Qur?an is not only a principal source of Islamic teachings pertaining to belief, Shari?ah and morals, but there are many cues in the Qur?an that encourage and inspire the advancement of human civilization. The Qur?an as a civilization that does not mean it contains the basic principles of science and civilization, one of which is to provide motivation and inspiration to study mathematics and arithmetic.The Qur?an uses numbers and figures are scattered in several verses, either in the form of fractions (al-kasur), unit numbers (al-mufrad), sequence numbers (at-tartibiyah), arranged numbers (murakkab) and dozens of numbers (al-uqd). The Qur?an also mentions 38 numbers, which can be grouped into seven groups of fractions, ie, unit numbers or numbers that only a single digit number composed (murakkab) of two numbers, numbers which are composed of three numbers, numbers which are composed of four numbers, numbers which are composed of five numbers, and numbers are made up of six digits. Some are repeated and there is a one-time mention. The meaning of these numbers there are two kinds of intrinsic meaning (truth) and the meaning of numbers of majazi.